Martin Escardo, 2012- Expanded on demand whenever a general equivalence is needed. \begin{code} {-# OPTIONS --without-K --exact-split --safe #-} open import SpartanMLTT open import Two-Properties open import UF-Base open import UF-Equiv open import UF-FunExt open import UF-Lower-FunExt open import UF-Subsingletons open import UF-Subsingletons-FunExt open import UF-PropIndexedPiSigma module UF-EquivalenceExamples where curry-uncurry' : funext 𝓤 (𝓥 ⊔ 𝓦) → funext (𝓤 ⊔ 𝓥) 𝓦 → {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } {Z : (Σ x ꞉ X , Y x) → 𝓦 ̇ } → Π Z ≃ (Π x ꞉ X , Π y ꞉ Y x , Z (x , y)) curry-uncurry' {𝓤} {𝓥} {𝓦} fe fe' {X} {Y} {Z} = qinveq c (u , uc , cu) where c : (w : Π Z) → ((x : X) (y : Y x) → Z (x , y)) c f x y = f (x , y) u : ((x : X) (y : Y x) → Z (x , y)) → Π Z u g (x , y) = g x y cu : ∀ g → c (u g) ≡ g cu g = dfunext fe (λ x → dfunext (lower-funext 𝓤 𝓦 fe') (λ y → refl)) uc : ∀ f → u (c f) ≡ f uc f = dfunext fe' (λ w → refl) curry-uncurry : (fe : FunExt) → {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } {Z : (Σ x ꞉ X , Y x) → 𝓦 ̇ } → Π Z ≃ (Π x ꞉ X , Π y ꞉ Y x , Z (x , y)) curry-uncurry {𝓤} {𝓥} {𝓦} fe = curry-uncurry' (fe 𝓤 (𝓥 ⊔ 𝓦)) (fe (𝓤 ⊔ 𝓥) 𝓦) Σ-≡-≃ : {X : 𝓤 ̇ } {A : X → 𝓥 ̇ } {σ τ : Σ A} → (σ ≡ τ) ≃ (Σ p ꞉ pr₁ σ ≡ pr₁ τ , transport A p (pr₂ σ) ≡ pr₂ τ) Σ-≡-≃ {𝓤} {𝓥} {X} {A} {x , a} {y , b} = qinveq from-Σ-≡ (to-Σ-≡ , ε , η) where η : (σ : Σ p ꞉ x ≡ y , transport A p a ≡ b) → from-Σ-≡ (to-Σ-≡ σ) ≡ σ η (refl , refl) = refl ε : (q : x , a ≡ y , b) → to-Σ-≡ (from-Σ-≡ q) ≡ q ε refl = refl ×-≡-≃ : {X : 𝓤 ̇ } {A : 𝓥 ̇ } {σ τ : X × A} → (σ ≡ τ) ≃ (pr₁ σ ≡ pr₁ τ) × (pr₂ σ ≡ pr₂ τ) ×-≡-≃ {𝓤} {𝓥} {X} {A} {x , a} {y , b} = qinveq from-×-≡' (to-×-≡' , (ε , η)) where η : (t : (x ≡ y) × (a ≡ b)) → from-×-≡' (to-×-≡' t) ≡ t η (refl , refl) = refl ε : (u : x , a ≡ y , b) → to-×-≡' (from-×-≡' u) ≡ u ε refl = refl Σ-assoc : {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } {Z : Σ Y → 𝓦 ̇ } → Σ Z ≃ (Σ x ꞉ X , Σ y ꞉ Y x , Z (x , y)) Σ-assoc {𝓤} {𝓥} {𝓦} {X} {Y} {Z} = qinveq c (u , (λ τ → refl) , (λ σ → refl)) where c : Σ Z → Σ x ꞉ X , Σ y ꞉ Y x , Z (x , y) c ((x , y) , z) = (x , (y , z)) u : (Σ x ꞉ X , Σ y ꞉ Y x , Z (x , y)) → Σ Z u (x , (y , z)) = ((x , y) , z) Σ-flip : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : X → Y → 𝓦 ̇ } → (Σ x ꞉ X , Σ y ꞉ Y , A x y) ≃ (Σ y ꞉ Y , Σ x ꞉ X , A x y) Σ-flip {𝓤} {𝓥} {𝓦} {X} {Y} {A} = qinveq f (g , ε , η) where f : (Σ x ꞉ X , Σ y ꞉ Y , A x y) → (Σ y ꞉ Y , Σ x ꞉ X , A x y) f (x , y , p) = y , x , p g : (Σ y ꞉ Y , Σ x ꞉ X , A x y) → (Σ x ꞉ X , Σ y ꞉ Y , A x y) g (y , x , p) = x , y , p ε : ∀ σ → g (f σ) ≡ σ ε (x , y , p) = refl η : ∀ τ → f (g τ) ≡ τ η (y , x , p) = refl Σ-cong : {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } {Y' : X → 𝓦 ̇ } → ((x : X) → Y x ≃ Y' x) → Σ Y ≃ Σ Y' Σ-cong {𝓤} {𝓥} {𝓦} {X} {Y} {Y'} φ = (F , (G , FG) , (H , HF)) where f : (x : X) → Y x → Y' x f x = pr₁ (φ x) g : (x : X) → Y' x → Y x g x = pr₁ (pr₁ (pr₂ (φ x))) fg : (x : X) (y' : Y' x) → f x (g x y') ≡ y' fg x = pr₂ (pr₁ (pr₂ (φ x))) h : (x : X) → Y' x → Y x h x = pr₁ (pr₂ (pr₂ (φ x))) hf : (x : X) (y : Y x) → h x (f x y) ≡ y hf x = pr₂ (pr₂ (pr₂ (φ x))) F : Σ Y → Σ Y' F (x , y) = x , f x y G : Σ Y' → Σ Y G (x , y') = x , g x y' H : Σ Y' → Σ Y H (x , y') = x , h x y' FG : (w' : Σ Y') → F (G w') ≡ w' FG (x , y') = to-Σ-≡' (fg x y') HF : (w : Σ Y) → H (F w) ≡ w HF (x , y) = to-Σ-≡' (hf x y) ΠΣ-distr-≃ : {X : 𝓤 ̇ } {A : X → 𝓥 ̇ } {P : (x : X) → A x → 𝓦 ̇ } → (Π x ꞉ X , Σ a ꞉ A x , P x a) ≃ (Σ f ꞉ Π A , Π x ꞉ X , P x (f x)) ΠΣ-distr-≃ {𝓤} {𝓥} {𝓦} {X} {A} {P} = qinveq ΠΣ-distr (ΠΣ-distr-back , ε , η) where η : ΠΣ-distr {𝓤} {𝓥} {𝓦} {X} {A} {P} ∘ ΠΣ-distr-back ∼ id η _ = refl ε : ΠΣ-distr-back ∘ ΠΣ-distr ∼ id ε _ = refl Σ+ : (X : 𝓤 ̇ ) (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) → (Σ x ꞉ X , A x + B x) ≃ ((Σ x ꞉ X , A x) + (Σ x ꞉ X , B x)) Σ+ X A B = qinveq f (g , η , ε) where f : (Σ x ꞉ X , A x + B x) → (Σ x ꞉ X , A x) + (Σ x ꞉ X , B x) f (x , inl a) = inl (x , a) f (x , inr b) = inr (x , b) g : ((Σ x ꞉ X , A x) + (Σ x ꞉ X , B x)) → (Σ x ꞉ X , A x + B x) g (inl (x , a)) = x , inl a g (inr (x , b)) = x , inr b η : g ∘ f ∼ id η (x , inl a) = refl η (x , inr b) = refl ε : f ∘ g ∼ id ε (inl (x , a)) = refl ε (inr (x , b)) = refl \end{code} The following name is badly chosen, and probably should have been used for the above: \begin{code} Σ+distr : (X : 𝓤 ̇ ) (Y : 𝓥 ̇ ) (A : X + Y → 𝓦 ̇ ) → (Σ x ꞉ X , A (inl x)) + (Σ y ꞉ Y , A (inr y)) ≃ (Σ z ꞉ X + Y , A z) Σ+distr X Y A = qinveq f (g , η , ε) where f : (Σ x ꞉ X , A (inl x)) + (Σ y ꞉ Y , A (inr y)) → (Σ z ꞉ X + Y , A z) f (inl (x , a)) = inl x , a f (inr (y , a)) = inr y , a g : (Σ z ꞉ X + Y , A z) → (Σ x ꞉ X , A (inl x)) + (Σ y ꞉ Y , A (inr y)) g (inl x , a) = inl (x , a) g (inr y , a) = inr (y , a) η : g ∘ f ∼ id η (inl _) = refl η (inr _) = refl ε : f ∘ g ∼ id ε (inl _ , _) = refl ε (inr _ , _) = refl Π-cong : funext 𝓤 𝓥 → funext 𝓤 𝓦 → (X : 𝓤 ̇ ) (Y : X → 𝓥 ̇ ) (Y' : X → 𝓦 ̇ ) → ((x : X) → Y x ≃ Y' x) → Π Y ≃ Π Y' Π-cong fe fe' X Y Y' φ = (F , (G , FG) , (H , HF)) where f : (x : X) → Y x → Y' x f x = pr₁ (φ x) g : (x : X) → Y' x → Y x g x = pr₁ (pr₁ (pr₂ (φ x))) fg : (x : X) (y' : Y' x) → f x (g x y') ≡ y' fg x = pr₂ (pr₁ (pr₂ (φ x))) h : (x : X) → Y' x → Y x h x = pr₁ (pr₂ (pr₂ (φ x))) hf : (x : X) (y : Y x) → h x (f x y) ≡ y hf x = pr₂ (pr₂ (pr₂ (φ x))) F : ((x : X) → Y x) → ((x : X) → Y' x) F = λ z x → pr₁ (φ x) (z x) G : ((x : X) → Y' x) → (x : X) → Y x G u x = g x (u x) H : ((x : X) → Y' x) → (x : X) → Y x H u' x = h x (u' x) FG : (w' : ((x : X) → Y' x)) → F (G w') ≡ w' FG w' = dfunext fe' FG' where FG' : (x : X) → F (G w') x ≡ w' x FG' x = fg x (w' x) HF : (w : ((x : X) → Y x)) → H (F w) ≡ w HF w = dfunext fe GF' where GF' : (x : X) → H (F w) x ≡ w x GF' x = hf x (w x) \end{code} An application of Π-cong is the following: \begin{code} ≃-funext₂ : funext 𝓤 (𝓥 ⊔ 𝓦) → funext 𝓥 𝓦 → {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } {A : (x : X) → Y x → 𝓦 ̇ } (f g : (x : X) (y : Y x) → A x y) → (f ≡ g) ≃ (∀ x y → f x y ≡ g x y) ≃-funext₂ fe fe' {X} f g = (f ≡ g) ≃⟨ ≃-funext fe f g ⟩ (f ∼ g) ≃⟨ Π-cong fe fe X (λ x → f x ≡ g x) (λ x → f x ∼ g x) (λ x → ≃-funext fe' (f x) (g x))⟩ (∀ x → f x ∼ g x) ■ 𝟙-lneutral : {Y : 𝓤 ̇ } → 𝟙 {𝓥} × Y ≃ Y 𝟙-lneutral {𝓤} {𝓥} {Y} = qinveq f (g , ε , η) where f : 𝟙 × Y → Y f (o , y) = y g : Y → 𝟙 × Y g y = (* , y) η : ∀ x → f (g x) ≡ x η y = refl ε : ∀ z → g (f z) ≡ z ε (o , y) = ap (_, y) (𝟙-is-prop * o) ×-comm : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } → X × Y ≃ Y × X ×-comm {𝓤} {𝓥} {X} {Y} = qinveq f (g , ε , η) where f : X × Y → Y × X f (x , y) = (y , x) g : Y × X → X × Y g (y , x) = (x , y) η : ∀ z → f (g z) ≡ z η z = refl ε : ∀ t → g (f t) ≡ t ε t = refl 𝟙-rneutral : {Y : 𝓤 ̇ } → Y × 𝟙 {𝓥} ≃ Y 𝟙-rneutral {𝓤} {𝓥} {Y} = Y × 𝟙 ≃⟨ ×-comm ⟩ 𝟙 × Y ≃⟨ 𝟙-lneutral {𝓤} {𝓥} ⟩ Y ■ +comm : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } → X + Y ≃ Y + X +comm {𝓤} {𝓥} {X} {Y} = qinveq f (g , η , ε) where f : X + Y → Y + X f (inl x) = inr x f (inr y) = inl y g : Y + X → X + Y g (inl y) = inr y g (inr x) = inl x ε : (t : Y + X) → (f ∘ g) t ≡ t ε (inl y) = refl ε (inr x) = refl η : (u : X + Y) → (g ∘ f) u ≡ u η (inl x) = refl η (inr y) = refl 𝟘-rneutral : {X : 𝓤 ̇ } → X ≃ X + 𝟘 {𝓥} 𝟘-rneutral {𝓤} {𝓥} {X} = qinveq f (g , η , ε) where f : X → X + 𝟘 f = inl g : X + 𝟘 → X g (inl x) = x g (inr y) = 𝟘-elim y ε : (y : X + 𝟘) → (f ∘ g) y ≡ y ε (inl x) = refl ε (inr y) = 𝟘-elim y η : (x : X) → (g ∘ f) x ≡ x η x = refl 𝟘-rneutral' : {X : 𝓤 ̇ } → X + 𝟘 {𝓥} ≃ X 𝟘-rneutral' {𝓤} {𝓥} = ≃-sym (𝟘-rneutral {𝓤} {𝓥}) 𝟘-lneutral : {X : 𝓤 ̇ } → 𝟘 {𝓥} + X ≃ X 𝟘-lneutral {𝓤} {𝓥} {X} = (𝟘 + X) ≃⟨ +comm ⟩ (X + 𝟘) ≃⟨ 𝟘-rneutral' {𝓤} {𝓥} ⟩ X ■ one-𝟙-only : (𝓤 𝓥 : Universe) → 𝟙 {𝓤} ≃ 𝟙 {𝓥} one-𝟙-only _ _ = unique-to-𝟙 , (unique-to-𝟙 , (λ {* → refl})) , (unique-to-𝟙 , (λ {* → refl})) +assoc : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {Z : 𝓦 ̇ } → (X + Y) + Z ≃ X + (Y + Z) +assoc {𝓤} {𝓥} {𝓦} {X} {Y} {Z} = qinveq f (g , η , ε) where f : (X + Y) + Z → X + (Y + Z) f (inl (inl x)) = inl x f (inl (inr y)) = inr (inl y) f (inr z) = inr (inr z) g : X + (Y + Z) → (X + Y) + Z g (inl x) = inl (inl x) g (inr (inl y)) = inl (inr y) g (inr (inr z)) = inr z ε : (t : X + (Y + Z)) → (f ∘ g) t ≡ t ε (inl x) = refl ε (inr (inl y)) = refl ε (inr (inr z)) = refl η : (u : (X + Y) + Z) → (g ∘ f) u ≡ u η (inl (inl x)) = refl η (inl (inr x)) = refl η (inr x) = refl +functor : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : 𝓦 ̇ } {B : 𝓣 ̇ } → (X → A) → (Y → B) → X + Y → A + B +functor f g (inl x) = inl (f x) +functor f g (inr y) = inr (g y) +cong : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : 𝓦 ̇ } {B : 𝓣 ̇ } → X ≃ A → Y ≃ B → X + Y ≃ A + B +cong {𝓤} {𝓥} {𝓦} {𝓣} {X} {Y} {A} {B} (f , (g , e) , (g' , d)) (φ , (γ , ε) , (γ' , δ)) = +functor f φ , (+functor g γ , E) , (+functor g' γ' , D) where E : (c : A + B) → +functor f φ (+functor g γ c) ≡ c E (inl a) = ap inl (e a) E (inr b) = ap inr (ε b) D : (z : X + Y) → +functor g' γ' (+functor f φ z) ≡ z D (inl x) = ap inl (d x) D (inr y) = ap inr (δ y) ×𝟘 : {X : 𝓤 ̇ } → 𝟘 {𝓥} ≃ X × 𝟘 {𝓦} ×𝟘 {𝓤} {𝓥} {𝓦} {X} = qinveq f (g , η , ε) where f : 𝟘 → X × 𝟘 f = unique-from-𝟘 g : X × 𝟘 → 𝟘 g (x , y) = 𝟘-elim y ε : (t : X × 𝟘) → (f ∘ g) t ≡ t ε (x , y) = 𝟘-elim y η : (u : 𝟘) → (g ∘ f) u ≡ u η = 𝟘-induction 𝟙distr : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } → X × Y + X ≃ X × (Y + 𝟙 {𝓦}) 𝟙distr {𝓤} {𝓥} {𝓦} {X} {Y} = f , (g , ε) , (g , η) where f : X × Y + X → X × (Y + 𝟙) f (inl (x , y)) = x , inl y f (inr x) = x , inr * g : X × (Y + 𝟙) → X × Y + X g (x , inl y) = inl (x , y) g (x , inr O) = inr x ε : (t : X × (Y + 𝟙)) → (f ∘ g) t ≡ t ε (x , inl y) = refl ε (x , inr *) = refl η : (u : X × Y + X) → (g ∘ f) u ≡ u η (inl (x , y)) = refl η (inr x) = refl Ap+ : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } (Z : 𝓦 ̇ ) → X ≃ Y → X + Z ≃ Y + Z Ap+ {𝓤} {𝓥} {𝓦} {X} {Y} Z (f , (g , ε) , (h , η)) = f' , (g' , ε') , (h' , η') where f' : X + Z → Y + Z f' (inl x) = inl (f x) f' (inr z) = inr z g' : Y + Z → X + Z g' (inl y) = inl (g y) g' (inr z) = inr z h' : Y + Z → X + Z h' (inl y) = inl (h y) h' (inr z) = inr z ε' : (t : Y + Z) → (f' ∘ g') t ≡ t ε' (inl y) = ap inl (ε y) ε' (inr z) = refl η' : (u : X + Z) → (h' ∘ f') u ≡ u η' (inl x) = ap inl (η x) η' (inr z) = refl ×comm : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } → X × Y ≃ Y × X ×comm {𝓤} {𝓥} {X} {Y} = f , (g , ε) , (g , η) where f : X × Y → Y × X f (x , y) = (y , x) g : Y × X → X × Y g (y , x) = (x , y) ε : (t : Y × X) → (f ∘ g) t ≡ t ε (y , x) = refl η : (u : X × Y) → (g ∘ f) u ≡ u η (x , y) = refl ×functor : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : 𝓦 ̇ } {B : 𝓣 ̇ } → (X → A) → (Y → B) → X × Y → A × B ×functor f g (x , y) = f x , g y ×-cong : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : 𝓦 ̇ } {B : 𝓣 ̇ } → X ≃ A → Y ≃ B → X × Y ≃ A × B ×-cong {𝓤} {𝓥} {𝓦} {𝓣} {X} {Y} {A} {B} (f , (g , e) , (g' , d)) (φ , (γ , ε) , (γ' , δ)) = ×functor f φ , (×functor g γ , E) , (×functor g' γ' , D) where E : (c : A × B) → ×functor f φ (×functor g γ c) ≡ c E (a , b) = to-×-≡ (e a) (ε b) D : (z : X × Y) → ×functor g' γ' (×functor f φ z) ≡ z D (x , y) = to-×-≡ (d x) (δ y) 𝟘→ : {X : 𝓤 ̇ } → funext 𝓦 𝓤 → 𝟙 {𝓥} ≃ (𝟘 {𝓦} → X) 𝟘→ {𝓤} {𝓥} {𝓦} {X} fe = qinveq f (g , ε , η) where f : 𝟙 → 𝟘 → X f * y = 𝟘-elim y g : (𝟘 → X) → 𝟙 g h = * η : (h : 𝟘 → X) → f (g h) ≡ h η h = dfunext fe (λ z → 𝟘-elim z) ε : (y : 𝟙) → g (f y) ≡ y ε * = refl 𝟙→ : {X : 𝓤 ̇ } → funext 𝓥 𝓤 → X ≃ (𝟙 {𝓥} → X) 𝟙→ {𝓤} {𝓥} {X} fe = qinveq f (g , ε , η) where f : X → 𝟙 → X f x * = x g : (𝟙 → X) → X g h = h * η : (h : 𝟙 → X) → f (g h) ≡ h η h = dfunext fe γ where γ : (t : 𝟙) → f (g h) t ≡ h t γ * = refl ε : (x : X) → g (f x) ≡ x ε x = refl →𝟙 : {X : 𝓤 ̇ } → funext 𝓤 𝓥 → (X → 𝟙 {𝓥}) ≃ 𝟙 {𝓥} →𝟙 {𝓤} {𝓥} {X} fe = qinveq f (g , ε , η) where f : (X → 𝟙) → 𝟙 f = unique-to-𝟙 g : (t : 𝟙) → X → 𝟙 g t = unique-to-𝟙 ε : (α : X → 𝟙) → g * ≡ α ε α = dfunext fe λ (x : X) → 𝟙-is-prop (g * x) (α x) η : (t : 𝟙) → * ≡ t η = 𝟙-is-prop * Π×+ : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : X + Y → 𝓦 ̇ } → funext (𝓤 ⊔ 𝓥) 𝓦 → (Π x ꞉ X , A (inl x)) × (Π y ꞉ Y , A (inr y)) ≃ (Π z ꞉ X + Y , A z) Π×+ {𝓤} {𝓥} {𝓦} {X} {Y} {A} fe = qinveq f (g , ε , η) where f : (Π x ꞉ X , A (inl x)) × (Π y ꞉ Y , A (inr y)) → (Π z ꞉ X + Y , A z) f (l , r) (inl x) = l x f (l , r) (inr y) = r y g : (Π z ꞉ X + Y , A z) → (Π x ꞉ X , A (inl x)) × (Π y ꞉ Y , A (inr y)) g h = h ∘ inl , h ∘ inr η : f ∘ g ∼ id η h = dfunext fe γ where γ : (z : X + Y) → (f ∘ g) h z ≡ h z γ (inl x) = refl γ (inr y) = refl ε : g ∘ f ∼ id ε (l , r) = refl +→ : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {Z : 𝓦 ̇ } → funext (𝓤 ⊔ 𝓥) 𝓦 → ((X + Y) → Z) ≃ (X → Z) × (Y → Z) +→ fe = ≃-sym (Π×+ fe) →× : {A : 𝓤 ̇ } {X : A → 𝓥 ̇ } {Y : A → 𝓦 ̇ } → ((a : A) → X a × Y a) ≃ Π X × Π Y →× {𝓤} {𝓥} {𝓦} {A} {X} {Y} = qinveq f (g , ε , η) where f : ((a : A) → X a × Y a) → Π X × Π Y f φ = (λ a → pr₁ (φ a)) , (λ a → pr₂ (φ a)) g : Π X × Π Y → (a : A) → X a × Y a g (γ , δ) a = γ a , δ a ε : (φ : (a : A) → X a × Y a) → g (f φ) ≡ φ ε φ = refl η : (α : Π X × Π Y) → f (g α) ≡ α η (γ , δ) = refl →cong : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {A : 𝓦 ̇ } {B : 𝓣 ̇ } → funext 𝓦 𝓣 → funext 𝓤 𝓥 → X ≃ A → Y ≃ B → (X → Y) ≃ (A → B) →cong {𝓤} {𝓥} {𝓦} {𝓣} {X} {Y} {A} {B} fe fe' (f , i) (φ , j) = H (equivs-are-qinvs f i) (equivs-are-qinvs φ j) where H : qinv f → qinv φ → (X → Y) ≃ (A → B) H (g , e , d) (γ , ε , δ) = F , (G , E) , (G , D) where F : (X → Y) → (A → B) F h = φ ∘ h ∘ g G : (A → B) → (X → Y) G k = γ ∘ k ∘ f E : (k : A → B) → F (G k) ≡ k E k = dfunext fe (λ a → δ (k (f (g a))) ∙ ap k (d a)) D : (h : X → Y) → G (F h) ≡ h D h = dfunext fe' (λ x → ε (h (g (f x))) ∙ ap h (e x)) →cong' : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {B : 𝓣 ̇ } → funext 𝓤 𝓣 → funext 𝓤 𝓥 → Y ≃ B → (X → Y) ≃ (X → B) →cong' {𝓤} {𝓥} {𝓣} {X} {Y} {B} fe fe' = →cong fe fe' (≃-refl X) pr₁-equivalence : (X : 𝓤 ̇ ) (A : X → 𝓥 ̇ ) → ((x : X) → is-singleton (A x)) → is-equiv (pr₁ {𝓤} {𝓥} {X} {A}) pr₁-equivalence {𝓤} {𝓥} X A iss = qinvs-are-equivs pr₁ (g , ε , η) where g : X → Σ A g x = x , pr₁ (iss x) η : (x : X) → pr₁ (g x) ≡ x η x = refl ε : (σ : Σ A) → g (pr₁ σ) ≡ σ ε (x , a) = to-Σ-≡ (η x , singletons-are-props (iss x) _ _) NatΣ-fiber-equiv : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → (x : X) (b : B x) → fiber (ζ x) b ≃ fiber (NatΣ ζ) (x , b) NatΣ-fiber-equiv A B ζ x b = qinveq (f b) (g b , ε b , η b) where f : (b : B x) → fiber (ζ x) b → fiber (NatΣ ζ) (x , b) f . (ζ x a) (a , refl) = (x , a) , refl g : (b : B x) → fiber (NatΣ ζ) (x , b) → fiber (ζ x) b g . (ζ x a) ((.x , a) , refl) = a , refl ε : (b : B x) (w : fiber (ζ x) b) → g b (f b w) ≡ w ε . (ζ x a) (a , refl) = refl η : (b : B x) (t : fiber (NatΣ ζ) (x , b)) → f b (g b t) ≡ t η b (a , refl) = refl NatΣ-vv-equiv : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → ((x : X) → is-vv-equiv (ζ x)) → is-vv-equiv (NatΣ ζ) NatΣ-vv-equiv A B ζ i (x , b) = equiv-to-singleton (≃-sym (NatΣ-fiber-equiv A B ζ x b)) (i x b) NatΣ-vv-equiv-converse : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → is-vv-equiv (NatΣ ζ) → ((x : X) → is-vv-equiv (ζ x)) NatΣ-vv-equiv-converse A B ζ e x b = equiv-to-singleton (NatΣ-fiber-equiv A B ζ x b) (e (x , b)) NatΣ-equiv : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → ((x : X) → is-equiv (ζ x)) → is-equiv (NatΣ ζ) NatΣ-equiv A B ζ i = vv-equivs-are-equivs (NatΣ ζ) (NatΣ-vv-equiv A B ζ (λ x → equivs-are-vv-equivs (ζ x) (i x))) NatΣ-equiv-converse : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → is-equiv (NatΣ ζ) → ((x : X) → is-equiv (ζ x)) NatΣ-equiv-converse A B ζ e x = vv-equivs-are-equivs (ζ x) (NatΣ-vv-equiv-converse A B ζ (equivs-are-vv-equivs (NatΣ ζ) e) x) NatΣ-equiv-gives-fiberwise-equiv : {X : 𝓤 ̇ } {A : X → 𝓥 ̇ } {B : X → 𝓦 ̇ } (φ : Nat A B) → is-equiv (NatΣ φ) → is-fiberwise-equiv φ NatΣ-equiv-gives-fiberwise-equiv = NatΣ-equiv-converse _ _ Σ-cong' : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) → ((x : X) → A x ≃ B x) → Σ A ≃ Σ B Σ-cong' A B e = NatΣ (λ x → pr₁ (e x)) , NatΣ-equiv A B (λ x → pr₁ (e x)) (λ x → pr₂ (e x)) NatΣ-equiv' : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → ((x : X) → is-equiv (ζ x)) → is-equiv (NatΣ ζ) NatΣ-equiv' A B ζ i = ((s , ζs), (r , rζ)) where s : Σ B → Σ A s (x , b) = x , pr₁ (pr₁ (i x)) b ζs : (β : Σ B) → (NatΣ ζ ∘ s) β ≡ β ζs (x , b) = ap (λ - → (x , -)) (pr₂ (pr₁ (i x)) b) r : Σ B → Σ A r (x , b) = x , (pr₁ (pr₂ (i x)) b) rζ : (α : Σ A) → (r ∘ NatΣ ζ) α ≡ α rζ (x , a) = ap (λ - → (x , -)) (pr₂ (pr₂ (i x)) a) Σ-change-of-variable' : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } (A : X → 𝓦 ̇ ) (g : Y → X) → is-hae g → Σ γ ꞉ ((Σ y ꞉ Y , A (g y)) → Σ A) , qinv γ Σ-change-of-variable' {𝓤} {𝓥} {𝓦} {X} {Y} A g (f , η , ε , α) = γ , φ , φγ , γφ where γ : (Σ y ꞉ Y , A (g y)) → Σ A γ (y , a) = (g y , a) φ : Σ A → Σ y ꞉ Y , A (g y) φ (x , a) = (f x , back-transport A (ε x) a) γφ : (σ : Σ A) → γ (φ σ) ≡ σ γφ (x , a) = to-Σ-≡ (ε x , p) where p : transport A (ε x) (back-transport A (ε x) a) ≡ a p = back-and-forth-transport (ε x) φγ : (τ : (Σ y ꞉ Y , A (g y))) → φ (γ τ) ≡ τ φγ (y , a) = to-Σ-≡ (η y , q) where q = transport (λ - → A (g -)) (η y) (back-transport A (ε (g y)) a) ≡⟨ i ⟩ transport A (ap g (η y)) (back-transport A (ε (g y)) a) ≡⟨ ii ⟩ transport A (ε (g y)) (back-transport A (ε (g y)) a) ≡⟨ iii ⟩ a ∎ where i = transport-ap A g (η y) ii = ap (λ - → transport A - (back-transport A (ε (g y)) a)) (α y) iii = back-and-forth-transport (ε (g y)) Σ-change-of-variable : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } (A : X → 𝓦 ̇ ) (g : Y → X) → is-equiv g → (Σ y ꞉ Y , A (g y)) ≃ Σ A Σ-change-of-variable {𝓤} {𝓥} {𝓦} {X} {Y} A g e = γ , qinvs-are-equivs γ q where γ : (Σ y ꞉ Y , A (g y)) → Σ A γ = pr₁ (Σ-change-of-variable' A g (equivs-are-haes g e)) q : qinv γ q = pr₂ (Σ-change-of-variable' A g (equivs-are-haes g e)) NatΠ-fiber-equiv : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → funext 𝓤 𝓦 → (g : Π B) → (Π x ꞉ X , fiber (ζ x) (g x)) ≃ fiber (NatΠ ζ) g NatΠ-fiber-equiv {𝓤} {𝓥} {𝓦} {X} A B ζ fe g = (Π x ꞉ X , fiber (ζ x) (g x)) ≃⟨ i ⟩ (Π x ꞉ X , Σ a ꞉ A x , ζ x a ≡ g x) ≃⟨ ii ⟩ (Σ f ꞉ Π A , Π x ꞉ X , ζ x (f x) ≡ g x) ≃⟨ iii ⟩ (Σ f ꞉ Π A , (λ x → ζ x (f x)) ≡ g) ≃⟨ iv ⟩ fiber (NatΠ ζ) g ■ where i = ≃-refl _ ii = ΠΣ-distr-≃ iii = Σ-cong (λ f → ≃-sym (≃-funext fe (λ x → ζ x (f x)) g)) iv = ≃-refl _ NatΠ-vv-equiv : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → funext 𝓤 (𝓥 ⊔ 𝓦) → ((x : X) → is-vv-equiv (ζ x)) → is-vv-equiv (NatΠ ζ) NatΠ-vv-equiv {𝓤} {𝓥} {𝓦} A B ζ fe i g = equiv-to-singleton (≃-sym (NatΠ-fiber-equiv A B ζ (lower-funext 𝓤 𝓥 fe) g)) (Π-is-singleton fe (λ x → i x (g x))) NatΠ-equiv : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) (ζ : Nat A B) → funext 𝓤 (𝓥 ⊔ 𝓦) → ((x : X) → is-equiv (ζ x)) → is-equiv (NatΠ ζ) NatΠ-equiv A B ζ fe i = vv-equivs-are-equivs (NatΠ ζ) (NatΠ-vv-equiv A B ζ fe (λ x → equivs-are-vv-equivs (ζ x) (i x))) Π-cong' : {X : 𝓤 ̇ } (A : X → 𝓥 ̇ ) (B : X → 𝓦 ̇ ) → funext 𝓤 (𝓥 ⊔ 𝓦) → ((x : X) → A x ≃ B x) → Π A ≃ Π B Π-cong' A B fe e = NatΠ (λ x → pr₁ (e x)) , NatΠ-equiv A B (λ x → pr₁ (e x)) fe (λ x → pr₂ (e x)) ≡-cong : {X : 𝓤 ̇ } (x y : X) {x' y' : X} → x ≡ x' → y ≡ y' → (x ≡ y) ≃ (x' ≡ y') ≡-cong x y refl refl = ≃-refl (x ≡ y) ≡-cong-l : {X : 𝓤 ̇ } (x y : X) {x' : X} → x ≡ x' → (x ≡ y) ≃ (x' ≡ y) ≡-cong-l x y refl = ≃-refl (x ≡ y) ≡-cong-r : {X : 𝓤 ̇ } (x y : X) {y' : X} → y ≡ y' → (x ≡ y) ≃ (x ≡ y') ≡-cong-r x y refl = ≃-refl (x ≡ y) ≡-flip : {X : 𝓤 ̇ } {x y : X} → (x ≡ y) ≃ (y ≡ x) ≡-flip = _⁻¹ , (_⁻¹ , ⁻¹-involutive) , (_⁻¹ , ⁻¹-involutive) singleton-≃ : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } → is-singleton X → is-singleton Y → X ≃ Y singleton-≃ {𝓤} {𝓥} (c , φ) (d , γ) = (λ _ → d) , ((λ _ → c) , γ) , ((λ _ → c) , φ) singleton-≃-𝟙 : {X : 𝓤 ̇ } → is-singleton X → X ≃ 𝟙 {𝓥} singleton-≃-𝟙 i = singleton-≃ i 𝟙-is-singleton singleton-≃-𝟙' : {X : 𝓤 ̇ } → is-singleton X → 𝟙 {𝓥} ≃ X singleton-≃-𝟙' = singleton-≃ 𝟙-is-singleton 𝟙-≡-≃ : (P : 𝓤 ̇ ) → funext 𝓤 𝓤 → propext 𝓤 → is-prop P → (𝟙 ≡ P) ≃ P 𝟙-≡-≃ P fe pe i = qinveq (λ q → Idtofun q *) (f , ε , η) where f : P → 𝟙 ≡ P f p = pe 𝟙-is-prop i (λ _ → p) unique-to-𝟙 η : (p : P) → Idtofun (f p) * ≡ p η p = i (Idtofun (f p) *) p ε : (q : 𝟙 ≡ P) → f (Idtofun q *) ≡ q ε q = identifications-of-props-are-props pe fe P i 𝟙 (f (Idtofun q *)) q empty-≃-𝟘 : {X : 𝓤 ̇ } → (X → 𝟘 {𝓥}) → X ≃ 𝟘 {𝓦} empty-≃-𝟘 i = qinveq (𝟘-elim ∘ i) (𝟘-elim , (λ x → 𝟘-elim (i x)) , (λ x → 𝟘-elim x)) complement-is-equiv : is-equiv complement complement-is-equiv = qinvs-are-equivs complement (complement , complement-involutive , complement-involutive) complement-≃ : 𝟚 ≃ 𝟚 complement-≃ = (complement , complement-is-equiv) domain-is-total-fiber : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } (f : X → Y) → X ≃ Σ (fiber f) domain-is-total-fiber {𝓤} {𝓥} {X} {Y} f = X ≃⟨ ≃-sym (𝟙-rneutral {𝓤} {𝓤}) ⟩ X × 𝟙 ≃⟨ Σ-cong (λ x → singleton-≃ 𝟙-is-singleton (singleton-types-are-singletons (f x))) ⟩ (Σ x ꞉ X , Σ y ꞉ Y , f x ≡ y) ≃⟨ Σ-flip ⟩ (Σ y ꞉ Y , Σ x ꞉ X , f x ≡ y) ■ total-fiber-is-domain : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } (f : X → Y) → (Σ y ꞉ Y , Σ x ꞉ X , f x ≡ y) ≃ X total-fiber-is-domain {𝓤} {𝓥} {X} {Y} f = ≃-sym (domain-is-total-fiber f) left-Id-equiv : {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } (x : X) → (Σ x' ꞉ X , (x' ≡ x) × Y x') ≃ Y x left-Id-equiv {𝓤} {𝓥} {X} {Y} x = (Σ x' ꞉ X , (x' ≡ x) × Y x') ≃⟨ ≃-sym Σ-assoc ⟩ (Σ (x' , _) ꞉ singleton-type' x , Y x') ≃⟨ a ⟩ Y x ■ where a = prop-indexed-sum (singleton-types'-are-props x) (singleton'-center x) right-Id-equiv : {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } (x : X) → (Σ x' ꞉ X , Y x' × (x' ≡ x)) ≃ Y x right-Id-equiv {𝓤} {𝓥} {X} {Y} x = (Σ x' ꞉ X , Y x' × (x' ≡ x)) ≃⟨ Σ-cong (λ x' → ×-comm) ⟩ (Σ x' ꞉ X , (x' ≡ x) × Y x') ≃⟨ left-Id-equiv x ⟩ Y x ■ pr₁-fiber-equiv : {X : 𝓤 ̇ } {Y : X → 𝓥 ̇ } (x : X) → fiber (pr₁ {𝓤} {𝓥} {X} {Y}) x ≃ Y x pr₁-fiber-equiv {𝓤} {𝓥} {X} {Y} x = fiber pr₁ x ≃⟨ Σ-assoc ⟩ (Σ x' ꞉ X , Y x' × (x' ≡ x)) ≃⟨ right-Id-equiv x ⟩ Y x ■ \end{code} Tom de Jong, September 2019 (two lemmas used in UF-Classifiers-Old) A nice application of Σ-change-of-variable is that the fiber of a map doesn't change (up to equivalence, at least) when precomposing with an equivalence. These two lemmas are used in UF-Classifiers-Old, but are sufficiently general to warrant their place here. \begin{code} precomposition-with-equiv-does-not-change-fibers : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {Z : 𝓦 ̇ } (e : Z ≃ X) (f : X → Y) (y : Y) → fiber (f ∘ ⌜ e ⌝) y ≃ fiber f y precomposition-with-equiv-does-not-change-fibers (g , i) f y = Σ-change-of-variable (λ x → f x ≡ y) g i retract-pointed-fibers : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {r : Y → X} → (Σ s ꞉ (X → Y) , r ∘ s ∼ id) ≃ (Π x ꞉ X , fiber r x) retract-pointed-fibers {𝓤} {𝓥} {X} {Y} {r} = qinveq f (g , (p , q)) where f : (Σ s ꞉ (X → Y) , r ∘ s ∼ id) → Π (fiber r) f (s , rs) x = (s x) , (rs x) g : ((x : X) → fiber r x) → Σ s ꞉ (X → Y) , r ∘ s ∼ id g α = (λ (x : X) → pr₁ (α x)) , (λ (x : X) → pr₂ (α x)) p : (srs : Σ s ꞉ (X → Y) , r ∘ s ∼ id) → g (f srs) ≡ srs p (s , rs) = refl q : (α : Π x ꞉ X , fiber r x) → f (g α) ≡ α q α = refl \end{code} Added 10 February 2020 by Tom de Jong. \begin{code} fiber-of-composite : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {Z : 𝓦 ̇ } (f : X → Y) (g : Y → Z) → (z : Z) → fiber (g ∘ f) z ≃ (Σ (y , _) ꞉ fiber g z , fiber f y) fiber-of-composite {𝓤} {𝓥} {𝓦} {X} {Y} {Z} f g z = qinveq ϕ (ψ , (ψϕ , ϕψ)) where ϕ : fiber (g ∘ f) z → (Σ w ꞉ (fiber g z) , fiber f (fiber-point w)) ϕ (x , p) = ((f x) , p) , (x , refl) ψ : (Σ w ꞉ (fiber g z) , fiber f (fiber-point w)) → fiber (g ∘ f) z ψ ((y , q) , (x , p)) = x , ((ap g p) ∙ q) ψϕ : (w : fiber (g ∘ f) z) → ψ (ϕ w) ≡ w ψϕ (x , refl) = refl ϕψ : (w : Σ w ꞉ (fiber g z) , fiber f (fiber-point w)) → ϕ (ψ w) ≡ w ϕψ ((.(f x) , refl) , (x , refl)) = refl fiber-of-unique-to-𝟙 : {𝓥 : Universe} {X : 𝓤 ̇ } → (u : 𝟙) → fiber (unique-to-𝟙 {_} {𝓥} {X}) u ≃ X fiber-of-unique-to-𝟙 {𝓤} {𝓥} {X} * = (Σ x ꞉ X , unique-to-𝟙 x ≡ *) ≃⟨ Σ-cong ψ ⟩ X × 𝟙{𝓥} ≃⟨ 𝟙-rneutral ⟩ X ■ where ψ : (x : X) → (* ≡ *) ≃ 𝟙 ψ x = singleton-≃-𝟙 (pointed-props-are-singletons refl (props-are-sets 𝟙-is-prop)) ∼-fiber-identifications-≃ : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {f : X → Y} {g : X → Y} → f ∼ g → (y : Y) (x : X) → (f x ≡ y) ≃ (g x ≡ y) ∼-fiber-identifications-≃ {𝓤} {𝓥} {X} {Y} {f} {g} H y x = qinveq α (β , (βα , αβ)) where α : f x ≡ y → g x ≡ y α p = (H x) ⁻¹ ∙ p β : g x ≡ y → f x ≡ y β q = (H x) ∙ q βα : (p : f x ≡ y) → β (α p) ≡ p βα p = β (α p) ≡⟨ refl ⟩ (H x) ∙ ((H x) ⁻¹ ∙ p) ≡⟨ (∙assoc (H x) ((H x) ⁻¹) p) ⁻¹ ⟩ (H x) ∙ (H x) ⁻¹ ∙ p ≡⟨ ap (λ - → - ∙ p) ((right-inverse (H x)) ⁻¹) ⟩ refl ∙ p ≡⟨ refl-left-neutral ⟩ p ∎ αβ : (q : g x ≡ y) → α (β q) ≡ q αβ q = α (β q) ≡⟨ refl ⟩ (H x) ⁻¹ ∙ ((H x) ∙ q) ≡⟨ (∙assoc ((H x) ⁻¹) (H x) q) ⁻¹ ⟩ (H x) ⁻¹ ∙ (H x) ∙ q ≡⟨ ap (λ - → - ∙ q) (left-inverse (H x)) ⟩ refl ∙ q ≡⟨ refl-left-neutral ⟩ q ∎ ∼-fiber-≃ : {X : 𝓤 ̇ } {Y : 𝓥 ̇ } {f : X → Y} {g : X → Y} → f ∼ g → (y : Y) → fiber f y ≃ fiber g y ∼-fiber-≃ H y = Σ-cong (∼-fiber-identifications-≃ H y) ∙-is-equiv-left : {X : 𝓤 ̇ } {x y z : X} (p : z ≡ x) → is-equiv (λ (q : x ≡ y) → p ∙ q) ∙-is-equiv-left {𝓤} {X} {x} {y} refl = equiv-closed-under-∼ id (refl ∙_) (id-is-equiv (x ≡ y)) (λ _ → refl-left-neutral) ∙-is-equiv-right : {X : 𝓤 ̇ } {x y z : X} (q : x ≡ y) → is-equiv (λ (p : z ≡ x) → p ∙ q) ∙-is-equiv-right {𝓤} {X} {x} {y} {z} refl = id-is-equiv (z ≡ y) \end{code}